Evaluación de la calidad del aire mediante el uso de líquenes como bioindicadores en tres parques del cantón Latacunga. - Zambrano Sandoval, Mayra Stephanie (2023)
At present, air pollution has a significant impact on the environment and health, being a significant problem, especially in urban areas due to population growth, industrial production, and CO2 emissions from the combustion of motor vehicles and industries that use petroleum-based fuels. Due to the nature of the research objectives, descriptive, bibliographic, and inductive research was applied in order to describe and analyze the current panorama of the effects of atmospheric pollution and the importance of the use of living organisms as bioindicators of air quality in addition to the non-experimental and trans-sectional methodologies. The results obtained made it possible to determine the level of atmospheric pollution in the canton of Latacunga. The main objective of this work was to evaluate the air quality in three parks in Latacunga using the Atmospheric Purity Index (API). This method is based on lichens as bioindicators by identifying alterations produced by atmospheric pollution in these communities. According to the method used, the lichen Ramalina Sp was identified as a species sensitive to pollution, as it does not have morphological structures for eliminating toxic substances when pollutants accumulate, causing the death of this species. In contrast, the species Candelaria concolor, Parmotrema austrosinense, Parmelia Sp and Heteroderma concolor, Parmelia Sp and Parmelia Sp were also identified as sensitive to pollution, Parmelia Sp and Heterodermia show medium sensitivity to become tolerant to atmospheric pollution, this is since they show symptoms of accumulation of particulate material, given that the resistance of the cell protoplasm and the maturity of the stems of these species determines the tolerance of non-vascular plants to different pollutants. The abundance of the lichen community, by itself, can express the air quality of a specific area as a qualitative method. In this case, as the Vicente León, San Francisco, and La Filantropía parks have the same atmospheric conditions, the same commercial activities, the same care and maintenance of the parks, and the same vehicular flow, it is determined that the atmospheric Contamination of the Latacunga canton presents values in the interval of 4-6 of the Atmospheric Purity Index, giving category III considered as Medium Contamination in the evaluated zones.